2019
DOI: 10.21273/jashs04683-19
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Population Structure Analysis of Bigleaf Hydrangea Using Genotyping-by-sequencing

Abstract: Hydrangea macrophylla (bigleaf hydrangea) is one of the most important floral and nursery crops worldwide. However, breeding of new bigleaf hydrangea cultivars has been hampered by a long breeding cycle and lack of genetic resources. This study investigated the genetic diversity and population structure of 82 bigleaf hydrangea cultivars using single-nucleotide polymorphisms (SNPs) originated from genotyping-by-sequencing. A total of 5803 high-quality SNPs were discovered in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…To date, SSR markers are still the most popular molecular marker type in hydrangea breeding programs, but their usefulness remains limited by low marker numbers 40 . Recently, a large number of SNPs were developed using GBS technology for ongoing genomic and breeding applications in hydrangea 29 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, SSR markers are still the most popular molecular marker type in hydrangea breeding programs, but their usefulness remains limited by low marker numbers 40 . Recently, a large number of SNPs were developed using GBS technology for ongoing genomic and breeding applications in hydrangea 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Genotyping of the hydrangea cultivar panel was carried out via GBS as described by Elshire et al 28 . A total of 5803 highquality SNPs discovered and described previously 29 were used to perform genome-wide association analysis in the present study.…”
Section: Plant Materials and Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…GBS has been employed for linkage mapping in woody ornamentals such as roses [20] and apples [21]. In hydrangea, it has been used for genetic diversity [22] and association mapping studies [23,24], but no linkage map was constructed with this method.…”
Section: Introductionmentioning
confidence: 99%
“…The fruit of a hydrangea is a capsule containing dozens to hundreds of ovules that are capable of maturation into viable seeds (Hufford, 2001). Hybrid seed production is often low in H. macrophylla, possibly due to inbreeding in the cultivated gene pool (Wu and Alexander, 2019). Jones et al (2007) reported from 0 to 20 seeds/ capsule while other researchers have reported as little as 0-5 seeds/ capsule resulting from crosses among H. macrophylla cultivars (Venturieri et al, 2017).…”
Section: Introductionmentioning
confidence: 99%